The Financial Channel of the Exchange Rate and Global Trade - Sai Ma; Tim Schmidt-Eisenlohr (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper provides evidence that the U.S. dollar affects countries' exports through the financial channel of the exchange rate (Bruno and Shin (2015)). Using global data on trade between countries whose currency is not the U.S. dollar, it documents a positive relationship between the dollar and import prices. Importantly, this effect is stronger when the dollar share of the exporter's foreign borrowing is larger. Results strengthen substantially when instrumenting the dollar by U.S. domestic housing activity. Then, a dollar appreciation increases import prices and decreases import quantities, with effects being proportional to the source country's foreign dollar borrowing share.
Keywords: F14; F31; G15; 330; dollar; dominant currency; financial channel; international trade